Anti-obesity effect of total phenylpropanoid glycosides from Ligustrum robustum Blume in fatty diet-fed mice via up-regulating leptin. (1st July 2015) - Yang, Run-mei; Liu, Fang; He, Zhen-dan; Ji, Min; Chu, Xin-xin; Kang, Zhuo-ying; Cai, Da-yong; Gao, Nan-nan
Abstract: Ethnopharmacological relevance: In Chinese folk medicine, the leaves of Ligustrum robustum Blume (LR) were commonly used in the treatment of obesity and hyperlipidemia. This study aimed to evaluate the anti-obesity effect and mechanisms of total phenylpropanoid glycosides from Ligustrum robustum Blume (LRTPG) in fatty diet-fed C57BL/6J mice. Materials and methods: C57BL/6J mice were divided randomly into 6 groups, i.e., control, model, positive (Orlistat 0.12 g/kg), and LRTPG at three dosages (0.3, 0.6 or 1.2 g/kg), respectively. Control mice were fed with standard diet; the others were fed with fatty diet. After 4 weeks׳ modeling, therapy mice were intragastrically administrated with positive drug or LRTPG for 5 weeks, respectively. Pharmacodynamic effects including body weight, fat weight, Lee׳s index, serum lipid levels, morphological changes and adipocyte area ratio were evaluated. The mechanisms were explored as the factors related to lipids metabolism in gene expressions by real-time PCR, and assured as the protein level of differential gene by Western blotting. Results: The anti-obesity effects of LRTPG in all treated mice were shown as decreased body weight, fat mass, Lee׳s index, total cholesterol (TC) level, and adipocyte area. The mechanisms were demonstrated as elevated mRNA and protein levels of adipose leptin, and consequently decreasing mRNA of adipose acyl coenzyme A: diacylglycerol acyltransferase (DGAT) with increasing mRNA of hepatic cholesterol 7α-hydroxylase (CYP7A1), which led to inhibition of triglyceride (TG) synthesis and promotion of cholesterol catabolism. Conclusions: The anti-obesity effect of LRTPG in fatty diet-fed mice was related to the up-regulation of leptin, which may provide scientific evidence supporting the traditional usage of LR on obesity in China. Graphical abstract: